Rapid Review of COVID-19 Vaccination Access and Acceptance for Global Refugee, Asylum Seeker and Undocumented Migrant Populations - Ariadne A. Nichol; Ariadne A. Nichol; Zoi Parcharidi; Wael K. Al-Delaimy; Elias Kondilis (Frontiers Media S.A., 2022)
Objectives: Refugees, asylum seekers, and undocumented migrants globally have been disproportionally impacted by COVID-19. Vaccination has been a major tool to reduce disease impact, yet concerns exist regarding equitable allocation and uptake.Methods: A rapid literature review was conducted based on PRISMA guidelines to determine COVID-19 vaccination acceptance rates and level of access for these population groups globally.Results: Relatively high COVID-19 vaccine acceptance levels were commonly reported in these populations, although, trust in host governments was a frequently expressed concern, especially for undocumented migrants. Outreach efforts and access to comprehensive information from a trusted source and in appropriate language were found to be major determinants of COVID-19 vaccine acceptance. COVID-19 vaccination access and policies varied considerably across host countries despite urgings by international organizations to include migrants and refugees. While most governments endorsed inclusive policies, evidence of successful program implementation was frequently lacking, creating difficulty to better tailor and implement COVID-19 outreach programs.Conclusion: This review identifies impactful improvements to be implemented to ensure equitable COVID-19 vaccinations and to reduce disease burden on refugees, asylum seekers, and undocumented migrants.